An Examination of the Impact of Debt Financing on the Performance of Small and Medium Enterprises in Mukono Municipality - Jacob Limo (Uganda Christian University, 2023)
This dissertation investigates the repercussions of debt financing on the productivity of Small and Medium-sized Enterprises (SMEs) in Mukono Municipality. SMEs are pivotal in economic development, yet they often encounter challenges in securing adequate financing. Debt financing, while potentially facilitating growth, can also introduce financial burdens. Employing a mixed-methods approach, combining quantitative analysis of financial data and qualitative insights from SME owners, this study delves into the effect of debt financing on revenue growth, employment generation, innovation, and overall sustainability of SMEs. It also explores the factors influencing SMEs' financing decisions, such as interest rates, collateral requirements, and contextual factors. The preliminary findings emphasize the significance of loan terms and conditions, providing insights to inform policies and practices conducive to sustainable debt financing for SMEs in Mukono Municipality, thereby contributing to regional economic development.
This is a dissertation.